A community-embedded approach to increasing the health literacy of Aboriginal children in a regional area: processes of co-design and local implementation - Good, Phillip; Grace, Rebekah; Kaplun, Catherine; Conti, Janet (Frontiers in Public Health, 2024)
This research explores the implementation of a child-centred, co-designed, communityembedded program called 'Young Doctors for Life' (YDFL). YDFL is designed to improve health and wellbeing outcomes for Aboriginal children in the middle childhood years. Focus is given in this paper to the processes of program adaptation of the YDFL to ensure local cultural relevance, drawing on the experiences and perspectives of children, parents, schoolteachers, and the implementation team. Method: Two focus groups with program stakeholders were convened. The first group consisted of three members from the local Aboriginal implementation team, and the second group comprised two members of the program design team. Children (n = 22) and schoolteachers (n = 2) participated in semi-structured interviews. Parent survey data (n = 16) were also collected and included. The data was analysed, guided by the five elements of implementation as outlined in the Hexagon Implementation framework (Capacity; Fit; Need; Usability; Support; and Evidence), which served as a priori themes.Results YDFL provides a promising example of how programs can be adapted with and for Aboriginal communities to support child health. Successful adaptation and implementation of this program required a co-design approach engaging program designers and the local implementation team. Community collaboration was also essential to identifying and addressing local community goals and aligning new programs with local service and cultural contexts. Conclusion: Health programs to support positive child outcomes are more likely to be successful when they share their focus between the risks and challenges within a community, and the positive, protective factors that can be leveraged to support children to flourish. Stakeholder engagement and community leadership are necessary to achieve meaningful program adaptation and implementation in Aboriginal communities.